Pembangunan Aplikasi Membeli-belah Barangan Runcit bagi Darek Enterprise - Md Jais, Anis Mirza; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2021)
Grocery Shopping Application is an application developed for customers to purchase groceries online. Buying groceries online is a new way to buy the desired groceries. Among the problems faced are crowded and irregular stores, making it difficult for customers to find the goods and products they want to buy. At Darek Enterprise, retailers do not have an effective method of managing order data. This is because retailers record order data manually using blank paper. In addition, they lack marketing channels. By looking at these weaknesses then the Grocery Shopping Application is developed. This application has been developed to help customers shop online without a time limit. Next, this Grocery Shopping Application has offered various product categories that can be browsed and selected by customers. This application also has a notification for customers to get the status of groceries purchased. In this project as well, there is a history log module that displays the purchase history for a customer. Based on the prototype methodology, the system was developed with the JAVA programming language, the Android Studio application, and the Firebase database to store data.The result of the project is to allow customers to place orders anywhere without time and place constraints. At the end of this project, Grocery Shopping Application was produced according to the needs of the users. This application will help improve the efficiency of goods order management for customers. Retailers can also promote products more widely.